2000
DOI: 10.1002/1096-8628(20001009)96:5<592::aid-ajmg3>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

The D2 dopamine receptor A1 allele and opioid dependence: Association with heroin use and response to methadone treatment

Abstract: A total of 95 Caucasian opioid-dependent patients were followed over a one-year period in an outpatient methadone treatment program. The frequency of the TaqI A(1) allele of the D(2) dopamine receptor (DRD2) gene was 19.0% in these patients compared with 4.6% in controls free of past and current alcohol and other drug abuse and free of family history of alcohol and other drug abuse (p = 0.009). Twenty-two of these patients dropped out of the methadone program (Group A), 54 had a successful treatment (Group B),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 39 publications
7
89
5
Order By: Relevance
“…Following a report ( Blum et al, 1990 ) that the A1 allele of the Taq1A polymorphism (rs1800497) of the DRD2 gene, a C-T substitution located in a noncoding region of the DRD2 locus, was associated with alcoholism, several studies have investigated the association of this polymorphism with substance use behavior, including tobacco ( Noble et al, 1994 ), opioid ( Lawford et al, 2000 ), and cocaine ( Noble et al, 1993 ) use. Despite the large number of individual studies investigating smoking behavior, however, results have been equivocal, and a recent meta-analysis suggested no evidence of association with cigarette smoking behavior ( M. Munafò, Clark, Johnstone, Murphy, & Walton, 2004 ), although another meta-analysis did suggest evidence of association with risk of alcohol dependence ( M. R. Munafò, Matheson, & Flint, 2007 ).…”
Section: Introductionsupporting
confidence: 90%
“…Following a report ( Blum et al, 1990 ) that the A1 allele of the Taq1A polymorphism (rs1800497) of the DRD2 gene, a C-T substitution located in a noncoding region of the DRD2 locus, was associated with alcoholism, several studies have investigated the association of this polymorphism with substance use behavior, including tobacco ( Noble et al, 1994 ), opioid ( Lawford et al, 2000 ), and cocaine ( Noble et al, 1993 ) use. Despite the large number of individual studies investigating smoking behavior, however, results have been equivocal, and a recent meta-analysis suggested no evidence of association with cigarette smoking behavior ( M. Munafò, Clark, Johnstone, Murphy, & Walton, 2004 ), although another meta-analysis did suggest evidence of association with risk of alcohol dependence ( M. R. Munafò, Matheson, & Flint, 2007 ).…”
Section: Introductionsupporting
confidence: 90%
“…The dopaminergic system, and in particular D2Rs, is well established to be important in reward circuitry and addiction. The A1 allele of the D2R, which has been linked with alcohol (Blum et al, 1990;Noble, 2003), nicotine (Spitz et al, 1998;Bierut et al, 2000), opioid (Lawford et al, 2000), psychostimulant (Persico et al, 1996;Noble, 2003), and polysubstance (Comings et al, 1991(Comings et al, , 1994O'Hara et al, 1993) abuse as well as pathologic gambling (Comings et al, 1996), has also been reported to be associated with an increase in AADC activity (Laakso et al, 2005).…”
Section: Trace Amines and Their Receptorsmentioning
confidence: 99%
“…The TaqI A RFLP has been associated with heroin use and methadone treatment outcome (Lawford et al, 2000), cocaine dependence (Noble et al, 1993), psychostimulant abuse (Persico et al, 1996), polysubstance abuse (O'Hara et al, 1993), and with early age of onset of multiple substance abuse (Comings et al, 1994). A DRD2 promoter region variant (-141⌬C) was associated with heroin use in Chinese subjects .…”
Section: Preproenkephalin Gene (Penk)mentioning
confidence: 99%